The analysis of trends and problems in higher education under the impact of globalization— the experiences of New Zealand and Taiwan - Wen-Jou, Hung (2011)
Năm 2007: Hội thảo lần I: Giáo dục đại học – Cơ hội và thách thức trong bối cảnh toàn cầu hóa và hội nhập